2016
DOI: 10.1111/jeu.12384
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Serine 148 in Giardia lamblia End‐binding 1 Protein is Important for Cell Division

Abstract: Giardia lamblia is a unicellular organism, showing a polarity with two nuclei and cytoskeletal structures. Accurate positioning of these organelles is essential for division of G. lamblia, which is poorly understood. Giardia lamblia end-binding 1 (GlEB1) protein and G. lamblia aurora kinase (GlAK) have been shown to modulate microtubule (MT) distribution during cytokinesis. A direct association between GlEB1 and GlAK was demonstrated. Like GlEB1, GlAK was also found at nuclear envelopes and median bodies of G.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Therefore, we examined the phenotype of the GlEB1 knockdown cells with respect to the formation of the flagella and median body in the following experiments. A previous study indicated that knockdown of the GlEB1 resulted in a cytokinesis defect (Kim et al, ). GlEB1 knockdown also resulted in an increased proportion of Giardia cells without a median body (from 24% to 30% p ‐value = 0.0012; Figure a(i)).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Therefore, we examined the phenotype of the GlEB1 knockdown cells with respect to the formation of the flagella and median body in the following experiments. A previous study indicated that knockdown of the GlEB1 resulted in a cytokinesis defect (Kim et al, ). GlEB1 knockdown also resulted in an increased proportion of Giardia cells without a median body (from 24% to 30% p ‐value = 0.0012; Figure a(i)).…”
Section: Resultsmentioning
confidence: 98%
“…The full length of recombinant GST‐tagged GlEB1 (GST‐GlEB1) protein was expressed in Escherichia coli BL21 (DE3) carrying pGEXEB1 1–238 (Kim et al, ) with 0.5 mM isopropyl β‐ᴅ‐1‐thiogalactopyranoside (IPTG) and purified using glutathione Sepharose ® 4B affinity chromatography (GE Healthcare, Uppsala, Sweden). GST protein was also purified as described above and used as a control.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations